2021
DOI: 10.1002/hbm.25584
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment intranetwork connectivity can predict the outcomes in idiopathic tinnitus patients treated with sound therapy

Abstract: Previous studies demonstrated that brain morphological differences and distinct patterns of neural activation exist in tinnitus patients with different prognoses after sound therapy. This study aimed to explore possible differences in intrinsic network‐level functional connectivity (FC) in patients with different outcomes after sound therapy (narrow band noise). We examined intrinsic FC using resting‐state functional magnetic resonance imaging in 78 idiopathic tinnitus patients (including 35 effectively treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 71 publications
1
23
0
Order By: Relevance
“…We speculate that this result may indicate that patients in the EG have a normal structural connection range and a longer functional connection range. For the remaining functional topological properties, consistent with some prior studies (Chen, Lv, et al, 2021a ; Lin et al, 2020 ), we speculate that structural injury emerges immediately after or in the early stage after tinnitus through the whole brain, while the functional network remains relatively intact in the same phase (Chen, Lv, et al, 2021a ; Straathof et al, 2019 ). The exact mechanism of this inconsistency needs to be further studied in the future.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…We speculate that this result may indicate that patients in the EG have a normal structural connection range and a longer functional connection range. For the remaining functional topological properties, consistent with some prior studies (Chen, Lv, et al, 2021a ; Lin et al, 2020 ), we speculate that structural injury emerges immediately after or in the early stage after tinnitus through the whole brain, while the functional network remains relatively intact in the same phase (Chen, Lv, et al, 2021a ; Straathof et al, 2019 ). The exact mechanism of this inconsistency needs to be further studied in the future.…”
Section: Discussionsupporting
confidence: 89%
“…Patients in the EG showed significant tinnitus symptom relief relative to patients in the IG (52.30% vs. −15.79%). More interestingly, using multimodal neuroimaging methods (a combination of SC, FC, and SC‐FC coupling), we found that except for brain structural changes (Chen, Lv, et al, 2021b ) and functional network‐level reorganization (Chen, Lv, et al, 2021a ), there were significant differences in brain SC network properties and SC‐FC couplings between the two groups; these differences were closely related to patient's outcomes. To the best of our knowledge, this is the first study exploring the distinct mechanisms of tinnitus patients with different outcomes after sound therapy from the perspective of functional‐structural connectome coalescence, employing combined DTI and rs‐fMRI methods.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations